Congestion control for multihop flows in wireless mesh networks - REN Juan; QIU Zheng-ding; WANG Sheng-hui (Tongxin xuebao)
A congestion control mechanism LAP （link layer adaptive pacing） for wireless mesh networks was presented,which controlled the transmission rate of wired-to-wireless flows at the mesh gateway to avoid serious interference among hops brought by excessive data transmission. The algorithm considered each flow as an object,which could not only improve the performance of multihop flows,but also keep network fairness. Besides,the control mechanism was re-alized at link layer and needn’t modify the existing transport or routing protocols. The simulation results showed that the network performance controlled by LAP exceeded 802.11 networks greatly,and outperformed current leading algorithms obviously too.